Gambaran Tingkat Pengetahuan Orang Tua Tentang Space Maintainer pada Anak - Adhara S alsa Delia; F. Loes Djimahit Sjahruddin; Fatimah Boenjamin (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Many parents think that primary teeth are not important because they will be replaced by permanent teeth. This view needs to be straightened out because even though primary teeth are temporary, primary teeth have an important function for children. Space maintainer is a tool that functions to maintain space due to premature loss of primary teeth so that permanent teeth can erupt in their place. Purpose: To describe the level of knowledge of parents about space maintainers in children. Methods: This type of research was observational descriptive with a cross-sectional design. Data collection was carried out to 100 people using consecutive sampling technique using a questionnaire on parents' knowledge about space maintainers in children which was directly distributed by the researcher to the respondents. Results: The results of the study were 50 respondents (50%) showing a good level of knowledge and 50 respondents (50%) had a less knowledge level related to space maintainers. Conclusion: The level of parental knowledge about dental and oral health is quite good, parental knowledge about teeth development is still lacking, and parental knowledge about space maintainers is quite good.